Using mental models in the analysis of human–wildlife conflict from the perspective of a social–ecological system in Namibia. Issue 1 (31st July 2013) - Mosimane, Alfons Wabahe; McCool, Stephen; Brown, Perry; Ingrebretson, Jane
Abstract: Human–wildlife conflicts occur within the context of a complex social–ecological system influenced by a wide variety of social, economic and political forces. Management responses to human–wildlife conflict are based on certain assumptions and perceptions that form the mental models of this system. Understanding these mental models provides opportunity for various stakeholders to engage management staff based on shared components and direct attention to areas of disagreement, and involve organizations that are normally considered to be outside the domain of human–wildlife conflict. Mind mapping was used in this study to identify mental models that people hold about human–wildlife conflict in Namibia, a country that has seen rapid increases in conflict, and to describe the principal factors and variables leading to such conflict. The results indicate that mind mapping is a useful tool for uncovering mental models of conflict and can reveal significant variables in reduction of conflict such as land-use planning and livelihood enhancement.